Assessment of immunological response to nutritional status in patients with stomach cancer qualified to the surgery - Ścisło, Lucyna; Walewska, Elżbieta; Orzeł-Nowak, Anita; Szczepanik, Antoni M.; Kłęk, Stanisław; Czupryna, Antoni (Nursing Problems / Problemy Pielęgniarstwa, 2013)
Introduction. Malnutrition is a frequent result of cancerous disease, especially upper digestive cancer, including stomach cancer. The consequences of malnutrition and a surgical injury are disorder of immune system and consequently the increased risk of occurrence of postoperative complications which extend the time of treatment and increase treatment expenses and may also lead to death in some cases. Therefore, recognition of malnutrition in patients complied with nutrition disorders in the perioperative period in malnourished patients has got significant influence on decreasing complications in the postoperative period. The aim of the study. The assessment of immunological response to nutritional status in patients with stomach cancer qualified to a surgery. Material and methods. The study included 99 patients with stomach cancer before the planned surgery. Nutritional status was evaluated with the screening method developed by Szczygieł on the basis of Thorsdottir. This test assesses percentage body mass loss, serum albumin concentration, the total count of peripheral blood lymphocytes, and measurement of fat mass and fat-free body mass. To assess immunological system’s parameters the concentration of selected cytokines: IL-6, IL-10, IL-12, IL-18 was examined as well as the concentration of tumor necrosis factor alpha — TNF-alpha — was marked. Results. In patients with stomach cancer occurs percentage loss of body weight, reduction of serum albumin concentration, reduction of the total number of leukocytes and malnutrition on the basis of nutrition interview. Well nourished patients had higher average values of IL-6, IL-12 and TNF-alpha, however lower average values of IL-10 and IL-18. Conclusion. Malnutrition in slight or moderate degree has been recognized in 30% of patients classified to a surgery due to stomach cancer. Changes of examined cytokines concentration in postoperative period indicate to immunological system’s reaction to malnutrition and surgical trauma. Nursing Topics 2013; 21 (1): 55–62